2022
DOI: 10.2147/idr.s344875
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Among Pathogens Causing Bloodstream Infections: A Multicenter Surveillance Report Over 20 Years (1998–2017)

Abstract: Purpose Bloodstream infections (BSIs) are a common consequence of infectious diseases and cause high morbidity and mortality. Appropriate antibiotic use is critical for patients’ treatment and prognosis. Long-term monitoring and analysis of antimicrobial resistance are important in guiding physicians to choose appropriate antibiotics and understand the changes in antimicrobial resistance and infection control. Here, we report a retrospective study on the trends of antimicrobial resistance in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous researchers paid attention to the monitoring of long-term antibiotics of Klebsiella pneumoniae, 11 the predictors of CRKP strain infection 12 , 13 and the effect of CRKP isolates on patients’ clinical relevance, 6 , 14–16 however, few studies have compared the differences between CRKP and CSKP strains in BSIs. Here, we conducted a retrospective case-control study in Guangdong Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers paid attention to the monitoring of long-term antibiotics of Klebsiella pneumoniae, 11 the predictors of CRKP strain infection 12 , 13 and the effect of CRKP isolates on patients’ clinical relevance, 6 , 14–16 however, few studies have compared the differences between CRKP and CSKP strains in BSIs. Here, we conducted a retrospective case-control study in Guangdong Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that the most common sites of MRSA infection are the respiratory tract (36.3%–48.0%), followed by the blood (15%–35.7%), wound or intravenous sites (25.2%–44%), and the urinary tract (2.8%–28%), while the least common source of MRSA isolates is puncture fluid (containing hydrothorax, ascites, pericardial fluid, cerebrospinal fluid, or articular cavity fluid; 21.32%) ( Rahimi and Shokoohizadeh, 2016 ; Huang et al., 2019 ; Samadi et al., 2019 ). MRSA is an important cause of bloodstream infections (BSI), and in 2009–2017, the MRSA detection rate was 40%–50% among BSI-associated S. aureus ( Zhang et al., 2022 ). Additionally, S. aureus was reported to be the main pathogen (67.5%) in paediatric osteomyelitis, and the proportion of MRSA among the cases due to S. aureus was 44% ( Chen et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolone resistance (FQR) was defined as resistance in vitro to ciprofloxacin and levofloxacin. 6…”
Section: Definition Of Specific Antimicrobial Resistance Phenotypesmentioning
confidence: 99%